2014
DOI: 10.1136/sextrans-2013-051368
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, correlates and trends in seroadaptive behaviours among men who have sex with men from serial cross-sectional surveillance in San Francisco, 2004–2011

Abstract: HIV seroadaptive behaviours remain common in San Francisco MSM, have increased in the last decade and are practiced differently by MSM with different sexual health knowledge and outcomes. Public health researchers and officials should continue to document the prevalence, intentionality, efficacy and safety of seroadaptive behaviours among diverse communities of MSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 36 publications
5
41
1
Order By: Relevance
“…Studies in North America that have employed a behavioral definition of pure serosorting have found that 8–31% of HIV-negative MSM and 12–21% of HIV-positive MSM engage in pure serosorting (1, 6, 15), while we noted a prevalence of 43% and 30%, respectively. The proportion of purposely-adopted pure serosorting in our study population (60% of visits by HIV-negative men and 34% visits by HIV-positive men), is slightly higher than two Swiss studies where 38–42% of men reported purposely-adopting pure serosorting (13, 14), The somewhat disparate findings between our study and others may be due to the different populations and time periods included in each study or different definitions used.…”
Section: Discussioncontrasting
confidence: 42%
“…Studies in North America that have employed a behavioral definition of pure serosorting have found that 8–31% of HIV-negative MSM and 12–21% of HIV-positive MSM engage in pure serosorting (1, 6, 15), while we noted a prevalence of 43% and 30%, respectively. The proportion of purposely-adopted pure serosorting in our study population (60% of visits by HIV-negative men and 34% visits by HIV-positive men), is slightly higher than two Swiss studies where 38–42% of men reported purposely-adopting pure serosorting (13, 14), The somewhat disparate findings between our study and others may be due to the different populations and time periods included in each study or different definitions used.…”
Section: Discussioncontrasting
confidence: 42%
“…Despite earlier concerns about an increase in heterosexual cases and "feminization" of the epidemic, it seems the actual scenario is the predominance of HIV infection among MSM, similar to data from many other countries [49,50]. In a study conducted in two Brazilian cities in 2013 using laboratory tests to distinguish recent from long-term infections, the estimated incidence rate was greater than 1% among MSM [25].…”
Section: Resultsmentioning
confidence: 94%
“…The availability of Internet sites and mobile applications for meeting sex partners that facilitate a high rate of sexual partner change and concurrency, particularly among MSM, 53,67 signals that healthcare providers should ask patients about how they meet their partners and counsel them about limiting the number of sex partners. Sexual behaviours among MSM with and without HIV, including serosorting and other seroadaptive behaviours, have emerged as a potential driver of the increase in syphilis in this population; 6870 it is not known if the availability of pre-exposure prophylaxis for HIV will lead to additional changes in sexual behaviour and in condom use among some MSM. 71,72 And last, among men at highest risk, it is not clear that behavioural interventions to increase condom use or reduce numbers of partners would be successful in achieving behaviour change or decreasing syphilis incidence.…”
Section: Key Prevention Interventions and How They Modify Syphilis Trmentioning
confidence: 99%